Is science multicultural? : postcolonialisms, feminisms, and epistemologies - Harding, Sandra G. (Bloomington, Ind. : Indiana University Press, 1998)
"Sandra Harding explores what practitioners of European/American, feminist, and postcolonial science and technology studies can learn from each other. She discusses the array of postcolonial science studies that have flourished over the last three decades and probes their implications for "northern" science."--Jacket
A Role for Postcolonial Histories of Science in Theories of Knowledge? Conceptual Shifts -- Postcolonial Science and Technology Studies: A Space for New Questions -- Voyages of Discovery: Imperial and Scientific -- Cultures as Toolboxes for Sciences and Technologies -- Postcolonial Feminist Science Studies: Resources, Challenges, Dialogues -- Are There Gendered Standpoints on Nature? -- Gender, Modernity, Knowledge: Postcolonial Standpoints -- Recovering Epistemological Resources: Strong Objectivity -- Borderlands Epistemologies -- Dysfunctional Universality Claims? Scientific, Epistemological, and Political Issues -- Robust Reflexivity.
Includes bibliographical references (pages 227-238) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Science -- Social aspects; Science -- History; Technology -- History; Feminism; Decolonization; Science -- sociology; Science -- history; Technology -- history; Feminism; Sciences -- Aspect social; Sciences -- Histoire; Technologie -- Histoire; Féminisme.; Décolonisation.; feminism; SCIENCE -- Philosophy & Social Aspects; Decolonization; Feminism; Science; Science -- Social aspects; Technology; Feminismus; Kulturimperialismus; Technik; Wissenschaft; Wissenschaftlich-technischer Fortschritt; Wissenschaftstheorie; Industriestaaten; Entkolonialisierung; Naturwissenschaften; Natuurwetenschappen; Culturele verschillen; Cultuur; Postkolonialisme; Sekseverschillen; Sciences -- Aspect social; Épistémologie.; Electronic books; History